(untitled) (Veterinary Science, 2023)
The objective of this work is to provide information about typical pathologies of senile big cats which can occur under human care since captivity often increases the life expectancy of the species. A case of an adult male African Lion is presented, which shows acute spinal cord ataxia and does not yield to anti-inflammatory analgesic therapy. Chemical containment is decided for the diagnostic route in order to show the possible cause of the disease in the animal. Clinical examination, hematological and biochemical profile are performed, in addition to serology of infectious diseases and radiographic examination under general anesthesia. The results show lesions in intervertebral discs compatible with multiple degenerative disc disease. Cited in the literature and in the results of this work, degenerative diseases can occur in senile big cats under human care. Complementary methods allow having a diagnosis and prognosis for decision making considering animal welfare. After diagnostic verification, the patient euthanasia is decided